Differences between lower body muscle potential during unloaded and loaded squat jump in elite male sprint swimmers - Durovic, M.; Nikolic, M.; Paunovic, M.; Madic, D.; Okicic, T. (Facta Universitatis: Series Physical Education and Sport, 2018)
The primary purpose was to determine differences between lower body muscle potential during the unloaded and loaded squat jump (SJ) in elite male swimmers. The secondary purpose was to assess the load that would maximize power output in the SJ. Twenty-one elite male trained competitive swimmers, all members of the Central Serbia Swimming Team (Age = 20.7 ± 3.8 yrs., Height = 1.84 ± 0.56 m, Weight = 77.5 ± 7.3 kg, FINA points 2017 long course = 636 ± 80) performed two trials of the unloaded and loaded SJ (barbell loads equal to 25 and 35% body weight). Loaded SJ testing with free weights was done using the Smith machine. The Myotest performance measuring system was used to calculate absolute and relative values of average power (Pavg, PavgRel) and maximal power (Pmax, PmaxRel) achieved during the unloaded and loaded SJ. The one-way ANOVA method and POST HOC (Tukey HSD) test were used. The results showed significant interactions between the unloaded and loaded squat jump for relative values of maximal power (F= 12.95, p= 0.000) and average power (F= 12.20, p= 0.000) as well as absolute values (F= 7.66, p= 0.001; F= 7.40, p= 0.001). The instantaneous power output in the SJ at 0% additional load (body weight) was significantly greater than that at 25% and 35% in the elite male trained competitive swimmers. The practical application of this study suggests that for male sprint swimmers, the load that generates maximal power output in the squat jump is body weight, without any additional load.